Characterization of cerate-zirconate ceramics powder prepared by three different methods: a comparative study - Nafisah Osman; Najwa ‘Adni Ibarahim; Mohd. Azlan Mohd. Ishak; Oskar Hasdinor Hassan (Universiti Kebangsaan Malaysia, 2014)
Ceramics powder of BaCe0.54Zr0.36Y0.1O2.95 (BCZY) was synthesized using three different methods namely sol-gel (SG), supercritical fluid (SC) and supercritical fluid assisted sol-gel (SCSG). The respective prepared samples were denoted as S1, S2 and S3. TG thermogram of the dried powders for all samples showed three stages of weight loss. Each stage was corroborated by one or two exothermic peaks as shown in DTG signal. Complete thermal decomposition for all the samples was almost accomplished at 1000°C for about 2 h. At calcination temperature of 1100°C, S1 showed a single-phase of perovskite-type oxides as proven by XRD result. Morphology of the calcined powders by SEM micrograph showed that S1 is in spherical shape, S2 is in cubic structure and S3 has a mixture of spherical and rod-like structure. Therefore, as comparison, SG method gives better characteristics of cerate-zirconate ceramics powder compared to SC and SGSC.